Analisis Reaksi Pasar Modal Indonesia Terhadap Pengumuman Kenaikan Suku Bunga The Fed: Studi Pada Perusahaan Kelompok Indeks Lq45 - Alifiani, Zulfa; Isynuwardhana, Deannes (eProceedings of Management, 2024)
Information was an indicator that can influence penanam modals' decisions when carrying out transctions in thecapital market. The importance of information made penanam modals consider various factors before makinginvestment decisions to reduce the risks they will receive. This research aims to find out how the capital marketreaction to the announcement of Fed's interest rate increase by seeing whether there are differences in abnormalreturns, trading volume activity, and security return variability. The objects used in this research are companiesin the LQ45 index group with a research period of 11 days, consisting of 5 days before, duringt, and 5 days afterthe event. The method used in this research is event study. The sampling technique used in this research waspurposive sampling and 39 companies were obtained. The hypothesis test used in this research is the WilcoxonSigned-Rank Test. The research results found that there were no difference in abnormal returns and tradingvolume activity in LQ45 companies before or after the announcement of the Fed's interest rate increase.However, there are differences in security return variability both before and after the announcement of the Fed'sinterest rate increase. Keyword-abnormal return, event study, security return variability, trading volume activity.